2013
DOI: 10.3389/fpsyg.2012.00593
|View full text |Cite
|
Sign up to set email alerts
|

Neurobiological Mechanisms Behind the Spatiotemporal Illusions of Awareness Used for Advocating Prediction or Postdiction

Abstract: The fact that it takes time for the brain to process information from the changing environment underlies many experimental phenomena of awareness of spatiotemporal events, including a number of astonishing illusions. These phenomena have been explained from the predictive and postdictive theoretical perspectives. Here I describe the most extensively studied phenomena in order to see how well the two perspectives can explain them. Next, the neurobiological perceptual retouch mechanism of producing stimulation a… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

1
11
0

Year Published

2014
2014
2022
2022

Publication Types

Select...
8

Relationship

2
6

Authors

Journals

citations
Cited by 8 publications
(12 citation statements)
references
References 48 publications
1
11
0
Order By: Relevance
“…13). This is in line with the proposal that illusory motion can be understood as a post-dictive perceptual phenomenon1718, in which the motion percept along the apparent motion trajectory is constructed after the stimuli have been presented. It has been further reported that perception of illusory motion is abolished when the fixation point falls on the apparent motion path, potentially because of the less precise representation of stimuli in the periphery.…”
Section: Resultssupporting
confidence: 89%
“…13). This is in line with the proposal that illusory motion can be understood as a post-dictive perceptual phenomenon1718, in which the motion percept along the apparent motion trajectory is constructed after the stimuli have been presented. It has been further reported that perception of illusory motion is abolished when the fixation point falls on the apparent motion path, potentially because of the less precise representation of stimuli in the periphery.…”
Section: Resultssupporting
confidence: 89%
“…However, the mere fact of different neural delay may be somewhat dubious (see Moutoussis and Zeki, 1997 ; Nishida and Johnston, 2002 ). Moreover, the situation seems to be a bit more complicated, and other factors such as whether stimulation comes in stream or flashed plays a role (Bachmann, 2010 , 2013 ; Bachmann et al, 2012 ).…”
Section: Flash-lag Effect Its Variations and Object Updatingmentioning
confidence: 99%
“…This paper is not meant to be an inclusive overview of backward phenomena in general (in the context of prediction vs. postdiction to cope adaptively with neural delay, see Bachmann ( 2013 ) for a systematic overview.) Rather, it aims to focus on the variety of phenomena at a wide range of time scales, to discuss possible underlying mechanisms as well as philosophical/real-world implications.…”
Section: Introductionmentioning
confidence: 99%
“…I will end the examples of illusions with the much celebrated flash-lag effect (FLE; Sheth et al, 2000 ; Nijhawan and Khurana, 2010 ; Bachmann, 2013 ; Hubbard, 2013 ). When an object continuously changes its feature value (e.g., location when in motion or color when presented from the same location) and an invariant object is briefly flashed, with its value matching the value of the changing object, the flashed object appears to lag behind the continuously changing object.…”
Section: The Phenomena To Be Explainedmentioning
confidence: 99%